China : Integrated Land Policy Reform in a Context of Rapid Urbanization - Guo, Li; Lindsay, Jonathan; Munro-Faure, Paul (World Bank, Washington, DC, 2012)
This report is about integrated land policy reform in context of rapid urbanization in China. Over the past thirty years, China has undergone a profound economic and social transformation as it moves towards a market-oriented economy. Land issues are implicated in this ongoing transformation in numerous ways. The allocation and security of land rights are key factors in China's quest for economic growth and social stability. Land use choices influence the shape and sustainability of China's rapidly growing cities, as well as the future prospects of its agriculture. Revenue generated from land plays a critical role in local government finances and affects the relationship between different levels of government. And increasingly, the growth and stability of the financial sector are linked to land-based transactions and financing arrangements. For the last four years, the Development Research Center of the State Council (DRC) and the World Bank have been working together to develop a deeper understanding of the role of land policy in China, and to identify options for moving forward on key land-related problems and opportunities. The spectacular growth of cities has been one of the most prominent features of China's recent history. From 1980 to 2005, the urban population grew from 19.4 percent to 43.0 percent. Urban growth has also been spatially dramatic, with the accelerating lateral expansion of cities resulting in the rapid conversion of agricultural land. The urban-rural interface defines an arena that is ideal for examining the complex interplay of all of China's most pressing land issues, including those of special relevance to the agricultural sector.